The complete chloroplast genome sequence of Didymocarpus yuenlingensis W. T. Wang 1982 - Weiqi Kuang; Jianjun Zhou; Lixuan Xiang; Huang Kerui; Du Deng (Mitochondrial DNA. Part B. Resources)
Didymocarpus yuenlingensis, a perennial plant in Gesneriaceae, is mainly found in Hunan, China, growing on stone cliffs. Its classification was traditionally based on morphology, lacking genetic data. This study sequenced its chloroplast genome (153,932 bp, GC 37.55%) and identified 133 genes, including 88 protein-coding genes. Phylogenetic analysis revealed its close relationship with D. sinoprimulinus and D. heucherifolius var. yinzhengii. These findings provide valuable genetic resources for understanding its evolutionary relationships and supporting future research on the Didymocarpus genus.